Mainstreaming Water Resources Management in Urban Projects : Taking an Integrated Urban Water Management Approach - World Bank Group (World Bank, Washington, DC, 2016)
This note provides guidance for cities in developing countries for managing the urban water cycle in a sustainable manner by using an Integrated Urban Water Management (IUWM) approach. After a brief introduction to the concept of IUWM, this note profiles the different IUWM approaches applied in three types of cities: a water-scarce, fast-developing city (Windhoek, Namibia), an expanding city subject to climate extremes (Melbourne, Australia) and a dense flood-prone city (Rotterdam, the Netherlands). It also profiles an example of World Bank engagement under an IUWM approach in a fast-growing city in a middle-income country (Vitoria in Espírito Santo, Brazil). The final section showcases a potential methodology for applying an IUWM approach in a city, from the initial engagement and diagnostic phases towards the application of a full IUWM umbrella framework under which a program can be implemented.